Comparison of risk factors and maternal outcomes in placenta previa: Assessing the impact of the revised classification in the Indian context - Tanvi Gupta; Vinita Udupa; Hilda Grace Yenuberi; Swati Rathore; Thenmozhi Mani (Journal of Current Research in Scientific Medicine)
Background: Placenta previa, characterized by the implantation of the placenta in the lower uterine segment close to or over the internal os, is a significant obstetric condition associated with maternal morbidity and mortality. This study aimed to compare the risk factors and outcomes of women with low-lying placenta (LLP) and true placenta previa (TPP) based on the revised classification in the Indian context. Materials and Methods: A retrospective study was conducted on patients diagnosed with traditional placenta previa at a tertiary care hospital in Vellore, India, between January 2006 and December 2016. The revised classification was applied, categorizing patients into LLP and TPP groups. Risk factors, including age, gravida, parity, previous cesarean sections, and previous placenta previa, were analyzed. Maternal outcomes such as mode of delivery, peripartum hemorrhage, and postpartum complications were assessed. Results: Among 888 women diagnosed with traditional placenta previa, 353 had LLP and 535 had TPP. Older age and previous cesarean delivery were significantly associated with TPP. Symptoms at presentation differed between the two groups, with LLP patients experiencing abdominal pain and leaking per vaginum, whereas TPP patients primarily presented with bleeding per vaginum. TPP was associated with a higher rate of cesarean deliveries, operative interventions, estimated blood loss, and the need for adjunct procedures, including peripartum hysterectomy. In addition, TPP was linked to longer hospital stays and a higher likelihood of intensive care unit admission. Conclusion: The revised classification of placenta previa offers improved risk assessment and enhances obstetric management. Women with TPP are at higher risk for adverse maternal outcomes compared to those with LLP. This study provides valuable insights into the Indian context, helping clinicians better understand the implications of the revised classification and tailor interventions for optimal maternal care.